Unraveling the role of social support in eating behavior among children and adolescents in Shanghai, China: exploring the mediating role of self-efficacy and the moderating influence of BMI and weight concern - Tan, Shuoyuan; Yang, Rui; Abdukerima, Gulqihra; Xu, Yimin; Zhu, Lihong; Xu, Bin; Shen, Wenwei; Song, Lixin; Ji, Bing; Wang, Zhaoxin; Chen, Chen; Shi, Jianwei (Frontiers in Nutrition, 2024)
Objective This study explores the intricate relationship between social support and eating behaviors in children and adolescents, considering the mediating role of eating self-efficacy and the moderating effects of body mass index (BMI) and weight concern. Methods Data from 1986 primary and secondary school students aged 8 to 17 in Shanghai, China, were analyzed using moderated mediation analysis. Results The results demonstrate a robust positive association between social support and eating self-efficacy, particularly prominent among individuals with low BMI (effect = 0.506, 95% CI [0.376, 0.636]). Moreover, the study highlights that eating behavior is influenced not only by eating self-control (β = −0.054, 95% CI [−0.062, −0.046]) but also by the interaction term between individuals’ perceptions of their body weight (β = −0.0008, 95% CI [−0.0015, −0.0001]). Conclusion Eating self-efficacy serves as a mediator in the relationship between social support and eating behavior, modulated by BMI and weight concern. Importantly, high weight concern significantly strengthens the mediating effect of eating self-efficacy on the relationship between social support and eating behavior, regardless of BMI.